Unmasking Logical Fallacies: An Analysis of The 2024 Indonesian Vice-Presidential Debates - Cholifah, Anjar Nur; Alfaruqy, Doni; Pustika, Reza; Sunarsih, Sunarsih (ppjbsip, 2024)
The logical fallacies that emerged in the 2024 Indonesian vice-presidential candidate debates is interested. By analyzing debate through a descriptive qualitative approach and employing Damer's (2009) classification theory, the study evaluates the presence of unconvincing arguments in the discourse of the three vice-presidential candidates. Logical fallacies, which are errors in reasoning, can obscure listeners and impact comprehension and the quality of arguments in a debate. Data were collected by transcribing argumentative speeches from two YouTube videos of the debates. There were 120 utterances produced by the three vice-presidential candidates. From 120 utterances, 60 logical fallacies were found. The findings reveal that the most prevalent logical fallacies included red herrings (16.67%), where candidates diverted attention from relevant topics to irrelevant ones. Ad hominem attacks (11.67%) were also common. Additionally, appeals to authority (11.67%) cited influential figures to support his argument on